2014
DOI: 10.57071/337arf
|View full text |Cite
|
Sign up to set email alerts
|

Attitude face au risque & Sciences économiques

Abstract: Ce document initie des lecteurs non-économistes aux théories de l'économie classique et comportementale du risque et de l'incertitude. Il décrit des résultats généralement acceptés en sciences économiques qui sont déterminants dans la prise de décision en conditions de risque ou d'incertitude et dans des situations où il est question de pertes et de gains. Pour illustrer ce sujet, sont présentés une sélection de résultats théoriques, entremêlés d'exemples de la vie quotidienne ainsi que des travaux de recherch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The expected utility theory originates from Bernoulli's postulate stating that the consequences of an event have a moral value or a utility greater than the monetary value for the economic agent in his decision-making (Olivero 2019). Based on precise axioms (comparability, transitivity, continuity, independence), was introduced two centuries later in economic theory by Von Neumann and Morgenstern, and dominated the decision-making modeling in risky situations (Chavas 2004;Concina 2014;Hardaker et al 2015). Abreha (2007) and Van Der Waal and Versluis (2017) showed that decision-making, whether it is the choice of the crop to produce or the quantity to produce, narrows down to the choice between different risky options given the decision maker's risk attitude.…”
Section: Risk Attitude Impacts Pathwaysmentioning
confidence: 99%
“…The expected utility theory originates from Bernoulli's postulate stating that the consequences of an event have a moral value or a utility greater than the monetary value for the economic agent in his decision-making (Olivero 2019). Based on precise axioms (comparability, transitivity, continuity, independence), was introduced two centuries later in economic theory by Von Neumann and Morgenstern, and dominated the decision-making modeling in risky situations (Chavas 2004;Concina 2014;Hardaker et al 2015). Abreha (2007) and Van Der Waal and Versluis (2017) showed that decision-making, whether it is the choice of the crop to produce or the quantity to produce, narrows down to the choice between different risky options given the decision maker's risk attitude.…”
Section: Risk Attitude Impacts Pathwaysmentioning
confidence: 99%
“…Une deuxième propriété importante de cette gestion des risques, son caractère collectif sera présentée dans la troisième partie. Ces caractéristiques démarquent l'approche ergonomique d'autres Regards --comme celui de l'économie par exemple [Concina 2014] -selon lesquels les attitudes et décisions face aux risques sont abordées de façon relativement statique et individuelle.…”
Section: Une Gestion Dynamique Des Situations à Risquesunclassified
“…Tax policy is generally concerned with financing public expenditure in the most efficient and equitable way possible (Tanzi & Zee 2000); for that to happen, all economic agents must respond to tax policy in the intended way. The policy is often made with the assumption that economic agents are risk neutral, that risk preference is homogenous across all citizens and that social preferences are homogenous and generally acceptable (Concina 2014). This is a general assumption of rationality as per classical economic theory.…”
Section: Introduction and Literature Backgroundmentioning
confidence: 99%